1995
DOI: 10.1161/01.str.26.11.2112
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Studies of Severely Hypometabolic Tissue Volumes After Permanent Middle Cerebral Artery Occlusion

Abstract: The extension of severely hypometabolic volume after middle cerebral artery occlusion reinforces the concept of a dynamic penumbra and suggests the existence of a relatively large window of therapeutic opportunity in which it may be possible to develop neuroprotective strategies. Our study suggests that maximum infarct volume is determined at some time between 24 hours and 17 days after permanent middle cerebral artery occlusion in anesthetized baboons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
73
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 35 publications
9
73
2
Order By: Relevance
“…Recently, state-of-the-art PET technology enabled perfusional and metabolic changes leading to infarction in permanent MCAO to be followed (Heiss et aI., 1994). In these studies, the cat MCAO model had more similarities to the observations from single-shot anecdotal examina tions of acute ischemic stroke in humans than MCAO in baboons, in which a more delayed and more mod erate decrease in flow and metabolism was observed and infarcts were induced variably and confined often only to the basal ganglia (Tenjin et aI., 1992;Pappata et aI., 1993;Touzani et al, 1995;Young et al, 1995 -Berlage (1995)]. However, the clin ical value of these new techniques in the evaluation of early ischemic damage must still be established in larger series (Warach et al, 1996).…”
Section: Discussion Experimental Modelmentioning
confidence: 94%
“…Recently, state-of-the-art PET technology enabled perfusional and metabolic changes leading to infarction in permanent MCAO to be followed (Heiss et aI., 1994). In these studies, the cat MCAO model had more similarities to the observations from single-shot anecdotal examina tions of acute ischemic stroke in humans than MCAO in baboons, in which a more delayed and more mod erate decrease in flow and metabolism was observed and infarcts were induced variably and confined often only to the basal ganglia (Tenjin et aI., 1992;Pappata et aI., 1993;Touzani et al, 1995;Young et al, 1995 -Berlage (1995)]. However, the clin ical value of these new techniques in the evaluation of early ischemic damage must still be established in larger series (Warach et al, 1996).…”
Section: Discussion Experimental Modelmentioning
confidence: 94%
“…Watabe et al (2002) showed that CBF images can be quantitated at much shorter interval than the previous protocol, typically at 90 secs, from sequential PET scanning Altman et al (1991) obtained OEF values of 0.5370.13 from arteriosinus blood sampling. Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Variations are because of the differences in monkey species, physiologic conditions, anesthetic agent used, PET scanner, and methodology; the current results clearly show that the DARG method can be used to determine these physiologic parameters with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The CBV correction was performed for rCBF, rCMRO 2 , and regional oxygen extraction fraction measurements.…”
Section: Positron Emission Tomography Analysis In Monkey Brainmentioning
confidence: 99%